2019
DOI: 10.21608/mvmj.2019.23.203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium and /or Chromium on reproductive organs and semen profiles of male albino rats

Abstract: To evaluate the potential hazards of cadmium and/or chromium on the reproductive system of adult male albino rat. Design: Randomized controlled study. Animals: Forty mature male albino rats weighing 260 ± 10 g. Procedures: Rats were allocated into four groups (ten animals each). Control group (group 1), group 2 received 4.4 mg kg -1 cadmium chloride, group 3 was given 2.5 mg kg-1 sodium dichromate and group 4 received combination of Cd (2.2 mg kg -1 ) and Cr (1.25mg kg -1 ) orally, once daily for 65 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…This observation suggests that CdCl 2 -exposure resulted in shrinkage of the testes with associated significant reduction of GSI and testicular weight in rats. The findings of this study are in agreement with those of previous studies which reported that Cd-exposure resulted in decreased testicular weight in animal models [1,33].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This observation suggests that CdCl 2 -exposure resulted in shrinkage of the testes with associated significant reduction of GSI and testicular weight in rats. The findings of this study are in agreement with those of previous studies which reported that Cd-exposure resulted in decreased testicular weight in animal models [1,33].…”
Section: Discussionsupporting
confidence: 93%
“…Cd is equally an established carcinogen in animals [7,16,37]. Cd-exposure resulted in decreased testicular weight [7,30], necrosis of spermatogenic epithelium and degenerations of testicular seminiferous tubules [7], depletion of germ cells, testicular necrosis, carcinogenesis and sterility in in vivo models, and adverse effects on testicular cells in in vitro models [1,33]. Specifically, Cd-induced testicular toxicity resulted in significant decreases of sperm count, sperm motility, testosterone synthesis, spermatogonia, Sertoli cells and Leydig cells in rat testis [23,40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cd-induced necrotic and degenerative changes could explain the loss of body weight and testicular weight via derangement in some testicular constructions, such as seminiferous tubules and Leydig cells, that typically account for 70 %–80 % of the testicular mass [ 45 ]. Moreover, the Cd-induced lipid peroxidation and oxidative damage could contribute to reproductive organ atrophy [ 46 ]. Yet, herein, rats given TiO 2 NPs exhibited a significant increase in body weight gain and testicular weight.…”
Section: Discussionmentioning
confidence: 99%